(Invited) Dual-Gate TFT for Chemical Detection. (23rd July 2018) - le Bihan, France; Donero, Laetitia; Le Borgne, Brice; De Sagazan, Olivier; Tessier, Pierre-Yves; El Mel, Abdel-Aziz; Kovacevic, Eva; Le Brizoual, Laurent
Abstract : Electronic devices have shown their interests to develop chemical and biological sensors based on electrical detection. Various field effect transistor structures applied to those detections exist and can be used in liquids, but have often a limited sensitivity, especially due to the Nernst limit. Dual gate field effect transistor allows to enhance this sensitivity by capacitive amplification. This paper describes the development of a field effect transistor based on polycrystalline silicon. Technological parameters as thicknesses and doping level are studied in order to obtain a good amplification. Polarization conditions are optimized in order to fit the requirements for testing in liquid media. The specific use of polycrystalline silicon as active layer can lead to a high amplification of charges and/or potential levels. A proof of sensing detection is obtain with pH measurement.